Trends in Perioperative Venous Thromboembolism Associated with Major Noncardiac Surgery - Smilowitz, Nathaniel R.; Gupta, Navdeep; Guo, Yu; Maldonado, Thomas S.; Eikelboom, John W.; Goldhaber, Samuel Z.; Bangalore, Sripal; Berger, Jeffrey S. (TH Open, 2017)
Background Venous thromboembolism (VTE) is a common vascular complication of noncardiac surgery.Methods We evaluated national trends in perioperative in-hospital VTE incidence, management, and outcomes using a large database of hospital admissions from the United States. Patients aged ≥ 45 years undergoing major noncardiac surgery from 2005 to 2013 were identified from the National Inpatient Sample. In-hospital perioperative VTE was defined as lower extremity deep vein thrombosis (DVT) or pulmonary embolism (PE), and the incidence was evaluated over time. Multivariable regression models with demographics and comorbidities as covariates were generated to estimate adjusted odds ratios (aOR).Results Major noncardiac surgery was performed in 9,431,442 hospitalizations that met inclusion criteria, and perioperative VTE occurred in 99,776 patients (1,057 per 100,000), corresponding to an annual incidence of ≈53,000 after applying sample weights. Over time, perioperative VTE per 100,000 surgeries increased by 135 (95% confidence interval [CI]: 107–163), from 925 in 2005 to 1,060 in 2013 (p for trend <0.001; aOR [for 2013 vs. 2005]: 1.22, 95% CI: 1.19–1.26), due to increases in nonfatal VTE rates (from 840 [per 100,000 surgeries] in 2005 to 987 in 2013; p for trend <0.001). Perioperative VTE occurred most frequently in patients undergoing thoracic (2.0%) and vascular surgery (1.8%). Mortality was higher in patients with VTE than those without VTE (aOR: 3.12, 95% CI: 3.05–3.20).Conclusion Perioperative VTE occurs in approximately 1% of patients ≥45 years undergoing major noncardiac surgery, with increasing incidence of nonfatal VTE over time.
Keywords: deep vein thrombosis; mortality; perioperative; pulmonary embolism; surgery; venous thromboembolism